2011
DOI: 10.3354/meps08854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depth, habitat, and water motion on the abundance and distribution of ciguatera dinoflagellates at Johnston Atoll, Pacific Ocean

Abstract: A major impediment to understanding the seemingly random occurrence of ciguatera toxicity is uncertainty regarding the field ecology of benthic dinoflagellates that introduce toxins into the coral reef food web. Although broad generalizations have been made, past studies have often yielded contradictory results, particularly between ecological patterns documented in the Pacific versus the Caribbean. This study employed standardized methodology to investigate the distribution and abundance of toxigenic benthic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 51 publications
6
36
0
Order By: Relevance
“…in the two study areas was very heterogeneous; the same was observed at Johnston Atoll, where Gambierdiscus spp. reached 4.00x10 2 cells g -1 WW (Richlen & Lobel, 2011). The maximum population densities observed in Yucatan waters were comparable to maxima reported for Gambierdiscus spp.…”
Section: Toxic Dinoflagellate Risk Assessmentsupporting
confidence: 78%
See 3 more Smart Citations
“…in the two study areas was very heterogeneous; the same was observed at Johnston Atoll, where Gambierdiscus spp. reached 4.00x10 2 cells g -1 WW (Richlen & Lobel, 2011). The maximum population densities observed in Yucatan waters were comparable to maxima reported for Gambierdiscus spp.…”
Section: Toxic Dinoflagellate Risk Assessmentsupporting
confidence: 78%
“…At Johnston Atoll in the Pacific Ocean, the abundance of Gambierdiscus spp. was negatively correlated with water motion (Richlen & Lobel, 2011 (20.5-22.7 o C). Curiously, the absence of Gambierdiscus spp.…”
Section: Toxic Dinoflagellate Risk Assessmentmentioning
confidence: 96%
See 2 more Smart Citations
“…The high concentrations of P. lima on Posidonia raise the problem of its sampling representativeness, since most monitoring programmes focused on the water column, which might lead to an underestimation of the species abundance (Marr et al 1992). P. lima concentrations showed a significant relationship between P. oceanica and the water column (R 2 =0.79), suggesting that the species, being a weekly swimming dinoflagellate that can even be affected by low water motion conditions (Richlen and Lobel 2011), might move from one compartment to another. The establishment of a direct relationship between the concentration of this species in the water column and on macrophytes allows us to assess the concentration in one compartment by referring to the concentration in the other one.…”
Section: Discussionmentioning
confidence: 99%